PORTRAYING ACADEMIC WRITING APPTITUDE AND THE PLAGIARISM ISSUES AMONG EFL STUDENTS - Kartin Lihawa; Karmila Machmud; Adimawati Helingo (University of Kuningan, 2023)
This article is the research result of teaching-learning Academic Writing to English Students Department, UNG in the fourth semester of 2020. This research objective is to enrich applying theories accessed from online books and international Journals by avoiding plagiarism in students’ writing essay as theoretical bases of their research. Besides, they would be able to communicate in the target language of writing skill as a maximum standard. There are three categories of the rubric to analyze essay in this qualitative method; a) choosing ideas in introductory sentences before taking quotations, b) accuracy diction selection, and c) linkage ideas in well sentences formulation after choosing the quotation/paraphrase. The result, from 25 students’ writing, there are 15 students who got value of A category (60%), 5 students with A- category (20%), 3 students got B+ category (12%), and 2 students got C (8%).